Understanding winter patterns of zooplankton Diel Vertical Migration (DVM) in a high Arctic fjord (Kongsfjorden, Svalbard) - Grenvald, Julie Cornelius (UiT The Arctic University of Norway, 2017)
The papers I and II of this thesis are not available in Munin. Paper I: Grenvald, J. C., Callesen, T. A., Daase, M., Hobbs, L., Darnis, G., Renaud, P., Cottier, F., Nielsen, T. G., Berge, J.: “Plankton community composition and vertical migration during polar night in Kongsfjorden”. Available in Polar Biology 2016, 39(10): 1879–1895. Paper II: Grenvald, J. C., Vader, A., Reinardy, H., Berge, J., Renaud, P., Gabrielsen, T. M.: “Does the cryptochrome 2 gene (cry2) act as a circadian clock gene in krill (Thysanoessa spp.) during polar night in Kongsfjorden (Svalbard)? (Manuscript). Recent Arctic studies contradict a long-held paradigm of winter quiescence by documenting activity at many trophic levels in the marine food web even during the darkest months of winter. Previous studies have failed to identify which species are performing patterns of vertical migrations during polar night in Kongsfjorden (Svalbard). In the present study, acoustic data supplemented by zooplankton net sampling demonstrated that polar night migration involved several migration patterns. Synchronized diel vertical migration (DVM) was present during the first and final parts of the polar night period, when day-night cycles were more distinct. During the darkest months of mid-winter, synchronized DVM was absent. Mid-winter migration patterns were restricted to surface waters, of unsynchronized character, and did not follow a clear diurnal pattern. Periodically, mid-winter migrations became more synchronized possibly due to enhanced light sources other than solar, such as lunar light. Copepods, chaetognaths and krill (Thysanoessa spp.) were abundant species but krill were responsible for the acoustic migration patterns. Spectral sensitivity tests showed that krill (T. inermis) were able to perceive solar background illumination during mid-winter. A clock gene investigated in krill required light to show circadian rhythmicity. The molecular and electrophysiological experiments suggested that polar night migration was exogenous governed by ...